2022
DOI: 10.1002/acm2.13631
|View full text |Cite
|
Sign up to set email alerts
|

RefineNet‐based 2D and 3D automatic segmentations for clinical target volume and organs at risks for patients with cervical cancer in postoperative radiotherapy

Abstract: Purpose An accurate and reliable target volume delineation is critical for the safe and successful radiotherapy. The purpose of this study is to develop new 2D and 3D automatic segmentation models based on RefineNet for clinical target volume (CTV) and organs at risk (OARs) for postoperative cervical cancer based on computed tomography (CT) images. Methods A 2D RefineNet and 3D RefineNetPlus3D were adapted and built to automatically segment CTVs and OARs on a total of 44 222 CT slices of 313 patients with stag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 39 publications
1
9
0
Order By: Relevance
“…DLAS models performed well in contouring cervical cancer CTV, with a DSC range of 0.68 to 0.89. 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 Only Chang et al showed one pretrained DLAS model that had DSC of 0.68. 31 Compared with manual contouring, DLAS models used demonstrated satisfactory, if not better, performance than manual contouring with improvements in DSC and HD.…”
Section: Resultsmentioning
confidence: 99%
“…DLAS models performed well in contouring cervical cancer CTV, with a DSC range of 0.68 to 0.89. 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 Only Chang et al showed one pretrained DLAS model that had DSC of 0.68. 31 Compared with manual contouring, DLAS models used demonstrated satisfactory, if not better, performance than manual contouring with improvements in DSC and HD.…”
Section: Resultsmentioning
confidence: 99%
“…4, whether it is cervical cancer or endometrial cancer, AttResCNet achieved the better automatic delineation performance among the evaluated models in the most of the slices. Additionally, in our study, we added oncologist clinical evaluation, which were not included in numerous studies [30][31][32][33].…”
Section: Discussionmentioning
confidence: 99%
“…Kim et al [10] evaluated the feasibility of automatic delineation of CTV for patients with endometrial and cervical cancer using atlas-based auto-segmentation (ABAS) algorithms, which are used in commercial software, making the research not accessible for many radiotherapy centers. DL-based networks were open-source, which were developed in many researches [11][12][13]. In addition, the cervical cancer automatic delineation DL models studies did not have external validation [10][11][12][13] and only few researches had clinical evaluation [9].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, deep‐learning‐based (DL) methods using Convolutional neural networks (CNN) have been applied to the segmentation of images of a variety of cancers 6–8 . In terms of cervical cancer, it has shown comparable performance to the expert delineation for some cervical cancer segmentation 9–14 . However, the performance of these auto‐segmentation networks is highly dependent on the training dataset, which is affected by the difference in physician contouring styles and the anatomic structure differences among patients 15,16 .…”
Section: Introductionmentioning
confidence: 99%
“… 6 , 7 , 8 In terms of cervical cancer, it has shown comparable performance to the expert delineation for some cervical cancer segmentation. 9 , 10 , 11 , 12 , 13 , 14 However, the performance of these auto‐segmentation networks is highly dependent on the training dataset, which is affected by the difference in physician contouring styles and the anatomic structure differences among patients. 15 , 16 In order to generalize the trained network to a variety of unseen patient cases, network training is usually based on a large enough training set of different patient cases.…”
Section: Introductionmentioning
confidence: 99%